Unintegrated HIV-1 DNA recruits cGAS via its histone-binding domain to escape innate immunity - Cyprien Jahan; Lucie Bonnet-Madin; Shinichi Machida; Bijan Sobhian; Suzie Thenin-Houssier; Monsef Benkirane (Proceedings of the National Academy of Sciences, 2025)
To ensure optimal replication and spread, viruses have evolved countermeasures to evade type 1 IFN-mediated antiviral activity. During the early viral replication cycle steps until uncoating, the HIV-1 core protects viral pathogen associated molecular patterns (viral RNA and reverse transcription products) from recognition by innate immune sensors, including cGAS. However, after capsid uncoating, unintegrated viral DNA (uvDNA) becomes accessible. Here, we show that HIV-1 uses chromatin-mediated cGAS inactivation as a mechanism to protect its uvDNA from innate immune activation.